REALITAS POLITIK DALAM MEDIA MASSA (Konstruksi Pemberitaan Media Massa Seputar 100 Hari Pemerintahan Jokowi-JK) - Yeshida Sapahuma, Nacota (Politika: Jurnal Ilmu Politik, 2015)
This journal focus on political news contruction about 100 days of Jokowi-JK’s cabinet by Kompas, Republika and Media Indonesia newspapers. This topic is quite interesting to be published because it is an early evaluation to new government’s work, and as a tool for citizen to measure government’s ability in their first 100 days. Since the 100 days of Jokowi-JK’s cabinet was an important issue, many electronic and printed mass media took it as a headline, so does Kompas, Republika and Media Indonesia. Every mass media has their own framing and characteristic to define 100 days of Jokowi-JK’s cabinet issue. Keywords: 100 days of Jokowi-JK, news construction, media framing analysis.